Dynamics Of Educational Supervision And Its Impact On Teacher Professionality: A Literature Review - Subni, Muhammad; Samosir, Esther Naomi; Turan, Septi Indrawani; Fitrianti, Fitrianti; Warman, Warman (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This paper delves into the pivotal role of educational supervision in facilitating ongoing professional development for teachers amidst the rapidly evolving educational landscape, characterized by diverse learning needs. Effective supervision, beyond enhancing teaching performance, empowers teachers to adapt their practices to meet the ever-changing needs of students, thus underpinning the importance of understanding educational supervision dynamics and their impact on teacher professionalism. The shift towards more collaborative and learning-oriented supervision approaches fosters a partnership between supervisors and teachers, promoting a supportive environment conducive to reflective practice and idea exchange. Furthermore, the integration of technology in educational supervision has emerged as a crucial factor in enriching professional development opportunities. Through a comprehensive literature review, this study aims to provide insights into current supervision dynamics, focusing on collaborative approaches, the role of technology, and strategies designed to bolster teacher professionalism. The synthesis presented aims to identify ways in which educational supervision can contribute to a more adaptive and sustainable learning environment, benefiting both teachers and students Keywords: Educational Supervision; Teacher Professional Development; Collaborative Approach; Technology in Supervision; Teacher Professionalism.